Modeling of Gas-Solid Turbulence Flow in Silo - Siti Ilyani, Rani; Jolius, Gimbun; B. A., Aziz (2013)
This paper presents a computational fluid dynamics (CFD) study of gas-solid turbulence flow in a silo. The simulations were performed using three different turbulent models namely, standard k-ε (SKE), RNG k-ε (RNG) and Realizable k-ε (RKE). The gravitational force, Saffman lift force and two-way coupling effect were employed. The influence of grid size, discretization, modeling strategies and solver were examined. An Eulerian-Lagrangian approach was used to model the particle flow using Disperse Phase Model (DPM). The predicted gas-solid flow patterns inside the silo chamber were found to be in good agreement to the experimental data adopted from literature. Good predictions were achieved using RNG k-ε with discrepancy around 4%.